2013
DOI: 10.1345/aph.1r621
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Potential Cytochrome P450–Mediated Drug-Drug Interactions in Older Hospitalized Patients with Polypharmacy

Abstract: The prevalence of potential CYP-mediated DDIs is high in geriatric patients with polypharmacy. The risk of DDIs increases as a function of the number of medications dispensed. Pharmacists' decision to intervene for potential CYP-mediated DDIs depends on clinical judgment in addition to the output from drug alert software programs, but may be facilitated by a single multicomponent, multidrug potential CYP-mediated DDI assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(147 citation statements)
references
References 21 publications
6
133
0
8
Order By: Relevance
“…This may be due to the nature of our study population, including very elderly patients with high multimorbidity and polypharmacy. Similar to our results, Doan et al33 showed that the prevalence of potential cytochrome P450-mediated drug interactions was 80% in elderly patients with polypharmacy. Although a high number of potential significant drug interactions were detected by the Micromedex database, in the LTCH most interactions were considered of minor clinical importance by the interdisciplinary team or risk-benefit analyses were justified by the clinical characteristics of these patients.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the nature of our study population, including very elderly patients with high multimorbidity and polypharmacy. Similar to our results, Doan et al33 showed that the prevalence of potential cytochrome P450-mediated drug interactions was 80% in elderly patients with polypharmacy. Although a high number of potential significant drug interactions were detected by the Micromedex database, in the LTCH most interactions were considered of minor clinical importance by the interdisciplinary team or risk-benefit analyses were justified by the clinical characteristics of these patients.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have shown that polypharmacy increases the number of adverse drug events, 72,73 including severe hypoglycemia, 63,74 drug-drug interactions, 75,76 interactions with coexisting comorbidities, 77 and patient costs. 78 In addition, the higher the number of medications, the less likely the patient will remain adherent with the treatment regimen.…”
Section: Resultsmentioning
confidence: 99%
“…More the medications that are prescribed, the more the possibility of irrational polypharmacy. A study conducted by Doan et al determined the probability of potent cytochrome P450 (CYP 450) interactions in older hospitalized people taking more than five concurrent medicines [14]. Potential drug-drug interactions were present in 80% of people taking more than five concurrent medicines.…”
Section: Discussionmentioning
confidence: 99%